Gene silencing by EZH2 suppresses TGF-β activity within the decidua to avert pregnancy-adverse wound healing at the maternal-fetal interface - Osokine, Ivan; Siewiera, Johan; Rideaux, Damon; Ma, Stephany; Tsukui, Tatsuya; Erlebacher, Adrian (Cell reports (Cambridge), 2022)
A little-appreciated feature of early pregnancy is that embryo implantation and placental outgrowth do not evoke wound-healing responses in the decidua, the specialized endometrial tissue that surrounds the conceptus. Here, we provide evidence that this phenomenon is partly due to an active program of gene silencing mediated by EZH2, a histone methyltransferase that generates repressive histone 3 lysine 27 trimethyl (H3K27me3) histone marks. We find that pregnancies in mice with EZH2-deficient decidual stromal cells frequently fail by mid-gestation, with the decidua showing ectopic myofibroblast formation, peri-embryonic collagen deposition, and gene expression profiles associated with transforming growth factor β (TGF-β)-driven fibroblast activation and fibrogenic extracellular matrix (ECM) remodeling. Analogous responses are observed when the mutant decidua is surgically wounded, while blockade of TGF-β receptor signaling inhibits the defects and improves reproductive outcomes. Together, these results highlight a critical feature of reproductive success and have implications for the context-specific control of TGF-β-mediated wound-healing responses elsewhere in the body. [Display omitted] •EZH2 prevents implantation from triggering wound-healing responses in the uterus•EZH2 prevents wound healing in the uterus by suppressing TGF-β activity•PRC2-generated H3K27me3 marks transcriptionally silence TGF-β target genes•Derepressed wound-healing responses in the uterus lead to pregnancy failure Osokine et al. demonstrate that the epigenetic regulator EZH2 renders decidual stromal cells resistant to wound-healing signals mediated by TGF-β. Loss of EZH2 from the decidua results in fibroblast activation, induction of TGF-β target genes, and pregnancy failure. In vivo TGF-βRI inhibition partially rescues these effects.